Organizational Culture and Work Commitment as A Predictor of Work Productivity of PT "X" Employees - Prasetyas, Fiesta Harissa Deonanda; Prapunoto, Susana (International Journal of Science and Society, 2024)
Organizations need to implement organizational culture and work commitment as one way to increase the work productivity of employees. This study aims to analyze organizational culture and work commitment as predictors of PT "X" employees' work productivity. This research approach is a quantitative-research. The sampling technique used in this research is nonprobability sampling with convenience sampling technique. The population was 340 employees, then the sample used in the study was 100 respondents. Data analysis using multiple linear regression analysis. The results showed that organizational culture and work commitment are simultaneously predictors of employee productivity at PT "X".